Pengaruh Rensponsivitas Aparatur, Transparansi Pelayanan, dan Akuntabilitas terhadap Kepuasan Masyarakat (Studi di Kantor Kecamatan Juli, Bireuen – Aceh, Saat dan Pasca Bencana Hidrometeorologi) - Muntazar Muntazar; M. Yusuf; Koko Bustami; Mahyu Danil (Singkite Journal, 2026)
Job satisfaction is a crucial aspect of an organization's work environment. It is related to staff responsiveness, service transparency, and accountability. Therefore, organizational management efforts should be considered in addressing this issue, including this research. So, how should organizational management efforts, which are currently experiencing hydrometeorological disasters, be taken into account in conditioning this situation, including this research being carried out. By applying quantitative methods through surveys and using a causal path model between the assumed variables, the problem can be addressed. The results showed that (1) there is a moderate causal relationship between the assumed variables, namely staff responsiveness, service transparency, and accountability, at the Juli sub-district office. This demonstrates the direct and indirect influence of these assumed factors on job satisfaction. (2) The respective effects of staff responsiveness on public satisfaction are 18.52%, service transparency 20.32%, and accountability 27.44%. (3) the contribution of staff responsiveness, service transparency, and accountability to public satisfaction is 31.6%.